PERANAN RESEARCHAND DEVELOPMENT (R&D) DAN STRUCTURAL EQUATIONMODEL (SEM) DALAM PENELITIAN PENGEMBANGAN KURIKULUM TINGKAT SATUAN PENDIDIKAN - Rosana, Dadan (Jurnal Cakrawala Pendidikan, 2016)
A curriculum consists of a number of interrelated complex components. The school-based curriculum has several components: curriculum and learning outcomes, class-based evaluation, teaching-learning activities, and school-based curriculum organization. These are completed with the establishment of curriculum networking, the development of curriculum supplements (e.g. syllabuses), professional trainings for educational practitioners, and the development of curriculum information system. The school-based curriculum implementation and development strategies should include all of them. Therefore, it is necessary to continuously conduct research on the school-based curriculum, especially when the curriculum starts to be implemented. There are two important points in the school-based curriculum development research. The first includes developing and validating all the instructional kits used in the school to ensure that - the kits are ready to use and effective, and the second involves the comprehensive analysis of all the variables influencing the success of education. For the first point, the.research and development (R&D) approach is appropriate in the development and validation of curriculum supplements. For the second point, regarding causal correlations among variables in education, the structural equation modeling is appropriate. There are a number of educational variables that cannot be directly measured; latent variables must be formulated through other measurable variables. If the variables cannot be directly measured, we have to form the variables by means of variable indicators that can be directly measured by using measurement modeling. Analyzing causal correlations among latent variables, we can use the structural equation modeling involving path analysis and measurement modeling